Web-Based Google Translate Inconsistencies in Bahasa-Arabic Translations from the ‎Arabic Thesis Writer's Perspective - Dinata, Rahmat Satria; Mizan, Ahmad Nur; Budiarti, Meliza; Husna, Ilya (UIN Syekh Wasil Kediri, Indonesia, 2023)
This research aims to reveal the inconsistencies of machine translation from the perspective of students who use web-based Google Translate in their Arabic thesis. This research has an impact on translation machine users from Arabic teachers and researchers to be more careful in using Google Translate when translating from Bahasa to Arabic, especially in inconsistent aspects. The researcher used a mixed method with an Explanatory Sequential Design‎ because after distributing questionnaires in collecting quantitative data to collect patterns of inconsistencies that occurred, it was important to explain the initial findings from the quantitative data qualitatively through interviews. ‎Quantitative data is analyzed using simple percentage statistics, then qualitative data is analyzed through four steps, namely data collection, reduction, presentation, and conclusion. The results of this research found that inconsistencies in web-based Google Translate translation results were found in four patterns. First, Google Translate is very inconsistent in translating terms that have the same meaning (mutarodifat), but the terms that appear in the translation results are often different, even within the same paragraph. Second, inconsistencies very often also occur in the aspects of mufrad, mutsanna and jamak, the Google translation machine cannot differentiate between the singularity and plurality aspects of the object being translated, so translation errors often occur where a singular word that should be translated as mufrad will instead become plural or on the contrary. Third, the translation machine does not recognize the gender of the subject in the translated sentence, so translation inconsistencies in the mudzakkar and mu'annats aspects occur very often. Inconsistencies in the gender aspect, as well as the mufrad, mutsanna, and jamak aspects, have an impact on the fourth error pattern, namely grammatical inconsistencies, namely errors in using the verb (fi'il) in a sentence. Of the four patterns of inconsistency, the term inconsistency is a new thing that has not been revealed much. The grammatical aspect is closely related to aspects of the singular or plural form as well as the masculine or feminine form which is the subject of the translated sentence and needs to be discussed further by other researchers.